Comparing the Properties of a Semiconductor Diode Laser to a HeNe Laser in the Optics Lab Context - Jarocki, Luke; Miller, Nathan A. (My University, 2018)
In this project, we compare the properties of Helium-Neon (HeNe) lasers and semiconducting diode lasers. HeNe lasers have traditionally been used in the educational optics laboratory, but we wanted to explore how well the less-expensive semiconductor diode lasers would work in this context. We begin with a review of the theoretical properties of lasers and the specific laser emission mechanisms of the two lasers under study. To determine if the alternative type of laser would be suitable, we performed the existing optics labs with the diode laser to see if it would give comparable results to the HeNe. The diode laser output wavelength was between 610-660 nanometers, which is similar to the HeNe’s wavelength of 632.8 nm. We explored the wavelength stability, beam intensity, and intensity distribution of the two lasers. We conclude with a discussion of the utility of the diode lasers in the educational laboratory.
Color poster with text, images, and graphs.
Keywords: Semiconductor lasers; Helium-neon lasers; Posters